Proposta de valor para produtos de cooperativas agropecuárias de leite: um framework para legitimação de mercado - Tassotti, Marcos Vinicius Barbosa (Universidade do Vale do Rio dos Sinos, 2025)
The main objective of this study is to propose a framework of marketing strategies to support the legitimization of the value proposition of dairy cooperative products in Rio Grande do Sul. Although legitimization and value proposition are topics with significant existing literature, the specific focus of this study remains underexplored, which highlights the relevance of this research. To achieve this, the Design Science Research (DSR) methodology was applied, as it allows for the creation of artifacts that interact with the real world and proved to be appropriate for the proposed objective. Data collection involved various stakeholders in the value chain, including cooperative employees responsible for managing the value proposition, sales representatives who connect the cooperative to the market, and customers, who are ultimately responsible for generating value. Additionally, as part of the validation process, the framework was evaluated by a panel of experts composed of a Ph.D. professor and a sales representative with extensive experience in the dairy industry. Among the main findings, the importance of clearly communicating symbolic and emotional values stood out, as these values, when well understood by consumers, can become decisive in purchase decisions. The framework proposes an integrated value proposition through a system in which cooperatives remain focused on communicating their values through economic and functional attributes, while larger entities, such as associations and representative industry organizations, focus their efforts on building a unified image of cooperativism at the national level. This communication should prioritize symbolic and emotional values, which have the potential to directly impact the legitimation of cooperativism as a differentiating element for cooperative products in the Brazilian dairy market.
Keywords: Proposta de valor; Cocriação de valor; Legitimação; Cooperativas de leite; Design Science Research (DSR); Value proposition; Value co-creation; Legitimation; Dairy Cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Administração